Protection of Children as Perpetrators of Drug Abuse in the Perspective of Law Number 35 of 2014 - I Gusti Ayu Dilla Susmita Dewi; Kadek Julia Mahadewi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Currently, drug abuse is very widespread and has damaged the community that is a user, not to mention children are now many victims. Lack of knowledge of narcotics, makes children often used as a tool to trick so as not to be suspected by the parties. Parents need to pay attention and education to children considering the role of parents is very important because children more often meet and interact with parents considering that children are the next generation of the nation, so direction must be given from an early age. In this study, the author used qualitative research methods, whose scope was to describe legal protection of children as drug abusers based on the author's previous journal. This study aims to find out what factors affect children as drug abusers. A form of legal protection for children who abuse drugs.